Administration of Bajakah (Spatholobus littoralis hassk) stem ethanol extract cream inhibited the increasing of mmp-1 expression and the reducing of collagen in male wistar rats (Rattus norvegicus) exposed to ultraviolet b - Milhanah Milhanah; Wimpie Pangkahila; Anak Agung Gde Putra Wiraguna; IGA Wiwiek Indrayani; IM Agus Eka Darwinata; I Wayan Weta (Indonesian Archives and Biomedical Sciences, 2021)
Background: Exposure to ultraviolet B (UV-B) rays causes skin aging characterized through increased free radical damaged. To prevent skin aging due to UV-B exposure, it is necessary to additionally provide antioxidants as a measure to inhibit the skin aging process. Bajakah tree (Spatholobus littoralis hassk) is one antioxidants sourche such as phenols, flavonoids, and tannins. The aim was to prove that the administration of Bajakah stem ethanol extract cream inhibits increasing MMP-1 expression and reduction of collagen number in male Wistar rats exposed to UV-B. Methods: A posttest control group study design was coducted in male rats (Rattus norvegicus), Wistar strain, aged 2-3 months, weigh 180-200gram which was divided randomly into two groups. The control group (n = 18) was exposed to UV-B rays and placebo cream (0.2 mg/cm2), while the treatment group (n = 18) was exposed to UV-B rays and Bajakah stem ethanol extract cream 15 % (0.2 mg/cm2). Both creams have aplied twice before and after exposure to UV-B rays (3 times a week, with 840 mJ/cm2) for 4 weeks. Twenty-four hours after the last day intervention, a punch biopsy of skin tissue was prepared for histological examination followed by immunohistochemical assay (for MMP-1) and Sirius red (for collagen) staining. Results: The expression of MMP-1 was significantly higher in the control group (24.3 ± 6.20%) compared to the treatment group (11.5 ± 3.21%), p<0.001. Furthermore, the number of collagen was statistically lower in the control group (63.1 ± 3.94%) compared to the treatment group (82.0 ± 3.02%), p<0.001. Conclusion: The administration of bajakah (Spatholobus littoralis hassk) stem ethanol extract cream inhibited the increasing of MMP-1 expression and the reducing of collagen cells in male Wistar rats (Rattus norvegicus) those were exposed to UV- B.